ASSESSING LONG-RUN GROWTH PROSPECTS FOR THE UK'S REGIONS. (November 2020) - Verikios, George; Hurst, Ian; Young, Garry
Abstract : The UK faces a number of economic challenges in the short to medium term. Prior to COVID-19, renegotiation of trading arrangements with the European Union was the most prominent of these. We build on existing macroeconomic analysis by assessing prospects for the UK's regions generated by combining a global macroeconometric model and a regional computable general equilibrium of the UK. A central macroeconomic scenario shows a national average annual GDP growth rate of 1.7 per cent to 2044. When the macroeconomic scenario is applied across regions, growth rates range from 1.6 per cent for Cambridge to 2.2 per cent for Pembrokeshire; the standard deviation is low at 0.07 per cent and the coefficient of variation is 0.04 per cent. In contrast, much wider variation is observed in the standard deviation for exports (0.36 per cent), investment (0.11 per cent) and consumption (0.14 per cent). The country results favour Scotland, which grows at an annual rate of 1.8 per cent, whereas Wales is the slowest growing of the countries at 1.7 per cent. Consistent with the macroeconomic analysis, international trade is the most important contributor to the regional variation in growth rates. We also analyse the effects of higher government consumption relative to the forecasts and find most regions are predicted to experience lower economic activity except the handful in which government consumption is a much higher share of GDP than average.